Building Bridges: Barriers to Parent Engagement Faced by Secondary Mathematics Teachers (LEARNing Landscapes, 2016)
Although parent engagement is widely supported by research, it is largely absent in the secondary mathematics classroom. Limited preservice teacher education and perceptions surrounding teacher professionalism are discussed as barriers to engaging parents. Math teachers are additionally inhibited by the antagonistic portrayal of parents in the literature and in the media, e ectively alienating parents in the minds of teachers. We suggest a shift in the language used to discuss math education and the positioning of parents regarding knowledge as a way to enable parent engagement and build relationships of trust, which can transform otherwise di cult exchanges between teachers and parents.
Keywords: parent; engagement; mathematics; education; trust